Italian translations od Ivo Vojnović's Dubrovačka trilogija - Malinar, Smiljka (2004)
The article is dealing with the translation od Ivo Vojnović's play Dubrovačka trilogija by the author himself and by Carmen Cronia.
Projekt MZOS
ENG